Hydrodynamic cavitation pre-treatment of urban waste: Integration with acidogenic fermentation, PHAs synthesis and anaerobic digestion processes. (August 2022) - Lanfranchi, A.; Tassinato, G.; Valentino, F.; Martinez, G.A.; Jones, E.; Gioia, C.; Bertin, L.; Cavinato, C.
Abstract: Urban waste can be valorized within a biorefinery approach, producing platform chemicals, biopolymers and energy. In this framework, hydrodynamic cavitation (HC) is a promising pre-treatment for improving biodegradability due to its high effectiveness and low cost. This paper deals with the effect of HC pre-treatment on the acidogenic co-fermentation process of thickened sewage sludge from a WWTP and seasonal vegetable waste from a wholesale market. Specifically, HC was assessed by testing two sets of parameters (i.e., treatment time of 30 and 50 min; vacuum pressure 1.4 and 2.0 bar; applied power 8 and 17 kW) to determine its effectiveness as a pre-treatment of the mixture. The highest increase in sCOD (+83%) and VFAs (from 1.93 to 17.29 gCODVFA L −1 ) was gained after 50 min of cavitation. Fermentations were conducted with not cavitated and cavitated mixtures at 37 °C on 4 L reactors in batch mode, then switched to semi-continuous with OLR of 8 kgTVS m- 3 d −1 and HRT of 5–6.6 d. Good VFAs concentrations (12.94–18.27 gCODVFA L −1 ) and yields (0.44–0.53 gCODVFA gVS(0) −1 ) were obtained, which could be enhanced by pre-treatment optimization and pH control. The organic acid rich broth obtained was then assessed as a substrate for PHAs storage by C. necator . It yielded 0.37 g g −1 of polyhydroxybutyrate, such biopolymer resulted to have analogous physicochemical characteristics of commercial equivalent. The only generated side-stream would be the solid-rich fraction of the fermented effluent, which valorization was assessed through BMP tests, showing a higher SGP of 0.42 Nm 3 kgTVS −1 for the cavitated. Graphical abstract: Image 1 Highlights: A mixture of sewage sludge and vegetable waste was pre-treated with cavitation. Cavitation pre-treatment raised the VFAs content of the mixture by nine folds. Cavitation-fermentation derived broth resulted performant for PHAs production. Cavitation raised the SGP of the solid-rich fraction of the fermented broth.